الدلالات التعليمية للكلمات العربية في الأفلام السينمائية الماليزية: الفنان بي. رملي نموذجاً / The educational implications of Arabic words in Malaysian Films: The Artist P. Ramlee as a model - Shehadeh Ali, Asem; ʿAbdul Fattāh Ibrahim ʿĪsā, Mahmūd (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2022)
ملخص البحث: تبحث هذه الدراسة في الدلالات التعليمية للكلمات العربية المتوفرة في أفلام الفنان الماليزي الشهير بي. رملي. وشحصيته؛ إذ لا يزال بي. رملي في أفلامه يحتل مساحة كبيرة في ذاكرة وضمير الشعب الماليزي بماليزيا، وهو فنان الشعب بلا منافسة، وقد قدم الفنان الراحل بي. رملي إسهاما كبيراً في نشر الكلمات العربية في رسالته؛ أما الأفلام التي لها مثلّ فيها وأخرجها فقد كان لها أثر كبير في انتشار الكلمات العربية بماليزيا؛ بالنظر إلى التقليد الشعبي للفنان بي. رملي وأفلامه أحياناً تحمل عناوين عربية بحتة. تسعى هذه الدراسة إلى توضيح استخدام الكلمات العربية في أفلام بي. رملي وشرح دلالاتها لمعرفة مدى تأثير الأفلام في استخدام الماليزيين للغة العربية من خلال المنهج الوصفي التحليلي. وخلصت الدراسة إلى أن هناك مفردات مشتركة بين الشعب الماليزي تعبّر عن اللغة العربية دون تغيير في معانيها ونطقها، وأن هناك كلمات تغيّر نطقها وبقي معناها، وأن الماليزيين وقعوا في حب اللغة العربية في أفلامه بسببها، وكان لنطقه وأدائه للكلمات في المؤلفات العربية بطريقة فكاهية وممتعة أثر كبير في انتشارها بين الملايويين، فضلاَ عن كون اللغة العربية لغة العبادة والدين بماليزيا، ووجدنا أن كثيراً من الكلمات غير متوافرة في قواميس لغة الملايو أو في كتاب الكتابة الجاوي المعتمد من مجمع اللغة الملايوية بماليزيا (Dewan Bahasa Dan Pustaka). الكلمات المفتاحية: المفردات العربية، المفردات المستعارة، بي. رملي، الأفلام، التأثيرات. Abstract This study examines the educational implications of Arabic words in the films and personality of the famous Malaysian artist P. Ramlee whose films still being remembered in the memory and conscience of the Malay people in Malaysia. He was a unique artist and had made a great contribution to the dissemination of Arabic words in his films, which to certain extent had affected the spread of the Arabic language in Malaysia considering the people’s imitation of his character. His films sometimes have purely Arabic titles. This study seeks to demonstrate the use of Arabic words in P. Ramlee films, and the explanation of its implications to know the extent of the impact of films on the use of Arabic by Malaysians through the descriptive analytical approach. The study concluded that there are common Arabic vocabularies in Malay that are being used without changing its meaning and pronunciation; there are also words whose pronunciation has changed but its meaning remains, and that the Malays were attracted to Arabic because of his films, his pronunciation, and his performance of words in Arabic compositions in a comic and fun way, in addition to being the language of worship and religion in Malaysia. Many of the words mentioned in P. Ramee’s films are not available in Malay dictionaries. Key words: Arabic vocabulary, borrowed vocabulary, P. Ramlee, The Films, The Impacts. Abstrak Kajian ini mengkaji implikasi pendidikan perkataan Arab yang terdapat dalam filem-filem artis terkenal Malaysia P. Ramlee, dan keperibadiannya. P. Ramlee dalam filem-filemnya masih mengambil ruang yang besar dalam ingatan dan hati nurani orang Melayu di Malaysia, dan beliau adalah seniman rakyat tanpa saingan, dan beliau memberi sumbangan yang besar dalam penyebaran perkataan Arab dalam filem-filemnya, yang menjejaskan penyebaran bahasa Arab di Malaysia memandangkan peniruan rakyat terhadap artis P. Ramlee dan filem-filemnya kadangkala bergelar Arab semata-mata. Kajian ini bertujuan untuk menunjukkan penggunaan perkataan Arab dalam filem P. Ramlee, dan penjelasan implikasinya untuk mengetahui sejauh mana kesan filem terhadap penggunaan bahasa Arab oleh rakyat Malaysia melalui pendekatan analisis deskriptif. Kajian tersebut merumuskan bahawa terdapat perbendaharaan kata yang lazim dalam kalangan masyarakat Malaysia yang menyatakan bahasa Arab tanpa mengubah makna dan sebutannya, dan terdapat perkataan yang telah berubah sebutannya dan maknanya kekal, dan orang Melayu telah jatuh cinta dengan bahasa Arab kerana filemnya, sebutannya, dan persembahan perkataannya dalam gubahan Arab dengan cara yang komik dan menyeronokkan, di samping menjadi bahasa ibadat, dan agama di Malaysia. Banyak perkataan yang disebut dalam filem P. Ramee tidak terdapat dalam kamus bahasa Melayu. Kata kunci: kosa kata Arab, kosa kata pinjaman, P. Ramlee, The Films, The Impacts.